SrcSlice: very efficient and scalable forward static slicing. Issue 11 (19th May 2014) - Alomari, Hakam W.; Collard, Michael L.; Maletic, Jonathan I.; Alhindawi, Nouh; Meqdadi, Omar; Oliveto, Rocco; Poshyvanyk, Denys
ABSTRACT A highly efficient lightweight forward static slicing approach is presented and evaluated. The approach does not compute the program/system dependence graph but instead dependence and control information is computed as needed while computing the slice on a variable. The result is a list of line numbers, dependent variables, aliases, and function calls that are part of the slice for all variables (both local and global) for the entire system. The method is implemented as a tool, called srcSlice, on top of srcML, an XML representation of source code. The approach is highly scalable and can generate the slices for all variables of the Linux kernel in approximately 20 min on a typical desktop. Benchmark results are compared with the CodeSurfer slicing tool from GrammaTech Inc., and the approach compares well with regard to accuracy of slices. Copyright © 2014 John Wiley & Sons, Ltd.